Influence disabling the cylynders of internal combustion engine on working process earthmovers machines - S. S. Zhuravlev (Вестник СибАДИ, 2017)
The article considers the effects of disabling the cylinder to change the characteristics of the engine earth-moving machines in various operating modes, calculated the diesel engines with subsequent analysis of their performance under different algorithms disable cylinders, evaluated the possibility of using additional flywheel to increase the technological parameters of the machine during operation.